Differences Between Non-Parental Male and Female Responses to Infant Crying - Anderson-Carter, India; Beroza, Alenna; Crain, Alex; Gubernick, Carly; Ranum, Elly; Vitek, Ross (Journal of Advanced Student Sciences (JASS), 2015)
The purpose of this study was to determine if there is a difference between how non-parental males and females between the ages of 20 and 24 respond physiologically to an audio recording of a crying infant. Based on previous research that investigated differences in physiological response of mothers and fathers to auditory stimuli of infants in distress, the difference between non-parental male and female physiological responses was studied. It was hypothesized that females would have a greater response in all three physiological variables studied. Within the experiment there were a total of 30 participants; 15 male and 15 female. While participants listened to a 30 second recording of an infant crying, measurements of brain activity, heart rate, and electrodermal activity were taken. Since a large number of studies measuring responses to infant stimuli were conducted using parents as subjects, the present experiment adds a new angle to a widely discussed topic. No significant difference was seen between males and females in any of the physiological variables that were measured.
An article that appeared in JASS, issue 2015
Keywords: audio; auditory; crying; emotion; EDA; EEG; pulse oximetry; sex; stress